Targeted and Effective Use of State and Non-State Social Funds - Gnatenko, Karina V.; Yaroshenko, Oleg M.; Inshyn, Mykola I.; Vapnyarchuk, Natalya M.; Sereda, Olena H. (International Journal of Criminology and Sociology, 2021)
Today, Ukraine is at the stage of forming a social and civil society. The main direction of state activity in the field of reforming Ukraine is the study, analysis and reform of the existing system of social services. The purpose of the study is to substantiate and summarise the main directions for the development of the system of financing social protection; to consider concepts such as “social protection”, “social insurance” and “social assistance”. To form and generalise knowledge about the existing system of financial and legal relations between the state and the population. To reveal the peculiarities of financing and directions of budget use in state and non-state social funds in a market economy. During the writing of the article, specific and general scientific methods of cognition were used to study and analyse the proposed topic. The method of generalisation, synthesis and analysis, observation, comparison and the method of scientific abstraction were used to evaluate and study the system of social funds in Ukraine. The system of social services in Ukraine was analysed. The existing system was analysed, weak points were revealed. Information on the foreign experience of developed countries in the field of providing social services to the population was considered. The current normative legal acts and laws were considered. Recommendations for the introduction of foreign experience in the existing system of social services have been developed. The study and analysis of the financing and functioning of the system of social protection and assistance to citizens provide an opportunity to understand how effectively it works. Assessing the effectiveness of state and non-state social funds should help identify weaknesses in the system and suggest a number of actions to improve their performance.